STRUCTURE AND USE OF THE MEDIUM-TERM PROJECTION MODEL IN THE NATIONAL BANK OF SERBIA - Đukić, Mirko; Momčilović, Jelena; Trajčev, Ljubica (Economic Annals, 2011)
Medium-term projections are an important element of the decision-making process in the inflation-targeting regime that the National Bank of Serbia has been implementing for the past several years. The main goal of medium-term projections is to project the policy rate path that will ensure that inflation in the coming period moves close to the targeted inflation rate. The most important tool for medium-term projections is a new Keynesian macroeconomic model, which is a set of equations aiming to describe the price-formation mechanism in Serbia and the transmission channel of monetary policy to prices. The model is comprised of four main behavioural equations for inflation, exchange rate, output gap, and policy rate, and of a number of side behavioural equations and identities. The model in the current form has been used since the end of 2008 and is subject to regular adjustments and improvements.